Hwa-Byung Treated by Using Ascending Kidney Water and Descending Heart Fire Pharmacopuncture: Three Case Studies - Jo, NaYoung (J Pharmacopuncture, 2017)
OBJECTIVES: We report the results of three case studies on the clinical effect of ascending kidney water and descending heart fire (AKDH) pharmacopuncture on patients with Hwa-Byung. METHODS: This study involved three patients, all female, who had been admitted to a hospital of traditional Korean medicine and had been diagnosed as having Hwa-Byung by using the Hwa-Byung Structure Clinical Interview for DSM-IV. AKDH pharmacopuncture is administered by injecting pharmacopuncture at a specific acupoint to change from a state of water-fire disharmony to one of water-fire harmony. For our three patients, Hwangyeonhaedoktang (黃連解毒湯) pharmacopuncture was injected at GB21 and GB20 on both sides; a total of 0.4 cc was injected, with 0.1 cc being injected at each point. Fel ursi, Bezora bovis and moschus (BUM) pharmacopuncture was injected at CV17, CV12, and CV6; a total of 0.15 cc was injected, with 0.05 cc being injected at each point. Treatment was done daily. Progress was evaluated using the Hwa-Byung diagnostic interview (HBDIS), beck depression inventory (BDI), and numeric rating scale (NRS) scores. RESULTS: For the first patient (case 1), after treatment, the HBDIS score was reduced from 44 to 30 points, the BDI score from 37 to 14, and the NRS score from 10 to 7. For the second patient (case 2), after treatment, the HBDIS score was reduced from 41 to 27 points, the BDI score from 13 to 7, and the NRS score from 10 to 5. For the third patient (case 3), after treatment, the HBDIS score was reduced from 42 to 28 points, the BDI score from 12 to 9, and the NRS score from 10 to 4. CONCLUSION: Ascending kidney water and descending heart fire pharmacopuncture treatment can be effective for improving ascending kidney water and descending heart fire energy and can be used to alleviate Hwa-Byung.